AGRO-ECOLOGICAL CHARACTERISTICS OF KARST REGIONS IN BOSNIA & HERZEGOVINA AND CLIMATE CHANGE (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Climate change researches indicate a significant increase in air temperature at the global level, while the annual precipitation shows a trend of decreased precipitation in the Mediterranean region. However, the local climate variability should be viewed as a consequence of global change determined by local impacts (latitude and longitude; topography; the impact of sea and altitude). In this paper agro-ecological characteristics of two individual regions namely the area of high karst with karst fields, and the area of low-Herzegovina area were analyzed. The analysis of climate change and variability covers representative weather stations of the observed regions: Livno, Mostar, and Trebinje. Short-term scenarios on climate change for these two regions for the period 2011-2040 (scenario RCP8.5, scenario A2, scenario A1B) were presented. The analysis of data shows that in the southern parts of Bosnia and Herzegovina, a higher level of climate variability is manifested. In particular, extremely high temperatures and solar radiation during the summer months, early moving of vegetation, the extension of dry periods during the early fall, while high rainfall occurred during the late fall and winter period. It creates many problems especially in the agricultural sector, so adaptation measures have to be developed focusing especially on the development of soil water management strategy.